Case Studies of Violence Against Children in Muslim Residential Schools - Putri Ramadhaniah; Meydina Inayyah; Amalia Dini; Nurlailatul Ramadhanti; Najla Un Nisa (International Journal of Southeast Asian Studies (IJSAS), 2022)
The method used in this research uses literature studies, primary legal materials and non-legal materials with a juridical normative approach. Primary legal materials in the form of laws and regulations and secondary legal materials in the form of literature materials in the form of reference books, national journals, and articles on online media, which are justified by non-legal materials in the form of legal phenomena of child violence that occur in Islamic boarding schools. The results of the study show that acts of persecution doesn't only occur in homes, public schools but also occur in religious schools. Cases of abuse that occur in Islamic boarding schools are a form of child violence committed by older people. Where the persecution not only causes physical violence but also causes death for the victim.